AN OVERVIEW OF THE IMPLEMENTATION OF THE POSTPARTUM FAMILY PLANNING PROGRAM AT BINJAI ESTATE PUBLIC HEALTH CENTER IN 2025 - Lormita Purba (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Postpartum family planning (PPFP) is a government-initiated contraceptive program aimed at reducing maternal mortality (MMR) and infant mortality (IMR), preventing unintended pregnancies, and maintaining appropriate birth spacing to minimize complications for both mothers and infants. In this study, the independent variables were the implementation of the postpartum family planning program based on characteristics such as age, education, parity, type of contraceptive method used, and whether counseling was received. The dependent variable was the postpartum family planning outcome. The results showed that the majority of PPFP users were aged 21–34 years (60.71%), with 13 respondents (46.43%) using implants, 3 (10.71%) using injectables, and 1 (3.57%) using an IUD. Among those under 20 years (7.14%), 1 respondent used an IUD and 1 used injectables. Among respondents over 35 years (32.14%), 7 used implants (25%), 1 used an IUD (3.57%), and 1 used injectables (3.57%). Mini pills, LAM, and condoms were rarely used among the participants at Binjai Estate Public Health Center. It is recommended that the Binjai Estate Public Health Center continue to strengthen and enhance the implementation of its postpartum family planning program.